Strategi Pemasaran Syariah Busana Muslim ‘Hana_Nadhira’ untuk Meningkatkan Profitabilitas - Giri Kurniadin; Sofian Muhlisin; Syarifah Gustiawati (Transformasi Manageria: Journal of Islamic Education Management, 2023)
Intense competition in the era of digital marketing and the use of social media requires entrepreneurs to adapt and formulate marketing strategies to survive and develop businesses. In the midst of business competition in capturing the market, fraud and fraudulent actions are vulnerable to be carried out. Moral and Islamic values are important to be implemented in the business operations that are carried out. Hana Nadhira is a business brand that was founded by a married couple and managed to take advantage of business opportunities through digital media with encouraging developments. This research is a qualitative research with the aim of analyzing how sharia marketing is implemented by Hana Nadhira Clothing in increasing profitability. The results of the research show that Hana Nadhira has succeeded in developing from a minimal profit with a narrow market coverage to a profitable business with a turnover of more than Rp. 50,000,000 per month and market penetrating overseas market. Continuous quality improvement in terms of products, promotions that are updated based on trends, as well as the use of communication media that is busy being used are the keys to the success of the business. Keywords: Sharia Marketing, Profitability